2007
DOI: 10.1007/s11055-007-0041-4
|View full text |Cite
|
Sign up to set email alerts
|

Local blood flow in the dorsal hippocampus and cerebellar cortex in the offspring of iodine-deficient rats

Abstract: Experimental studies demonstrated that hypothyroidism can lead to depressive behavior and that thyroid hormones can have antidepressant effects. Postnatal changes in local blood flow in the dorsal hippocampus and cerebellar cortex were studied in the offspring of rats kept in conditions of iodine deficiency at conception and throughout gestation. The data obtained from these studies showed that severe limitation of iodine intake before and during gestation leads to marked deficiency in the blood supply to both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Thyroid hormones are essential for the development and proper functioning of the central nervous system through their role in gene expression, myelin production, axonal transportation, and neurotransmission [7]. Although less investigated, hypothyroidism may also cause a reduction in flow and vessel density of the central nervous system [8,9]. Since the retina and optic nerves represent an extension of the central nervous system, one can suggest that hypothyroidism may cause alterations in retinal microstructure and perfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid hormones are essential for the development and proper functioning of the central nervous system through their role in gene expression, myelin production, axonal transportation, and neurotransmission [7]. Although less investigated, hypothyroidism may also cause a reduction in flow and vessel density of the central nervous system [8,9]. Since the retina and optic nerves represent an extension of the central nervous system, one can suggest that hypothyroidism may cause alterations in retinal microstructure and perfusion.…”
Section: Introductionmentioning
confidence: 99%
“…But there are also studies where no significant correlation between thyroid function and Alzheimer's disease was observed (18). Thyroid status may also be relevant to the pathophysiology of vascular dementia since mild hypothyroidism is associated with a decrease in cerebral blood flow (19,20). Little is known about the role THs play in mixed dementia, where AD is associated with cerebrovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…The investigators noted a significant decrease in brain blood vessel numbers in hypothyroid animals relative to controls. More recently, Gabrichidze et al (12) reported the effects of local blood flow in the hippocampus and cerebellar cortex of rats made hypothyroid during development by feeding the dams an iodine-deficient diet. In 1-mo-old hypothyroid offspring rats, blood flow in the dorsal hippocampus was 19% lower and 14% lower in the cerebellar cortex compared with those of agematched euthyroid rats.…”
mentioning
confidence: 99%